Dynamic prediction pools: An investigation of financial frictions and forecasting performance - Marco Del Negro; Raiden B. Hasegawa; Frank Schorfheide (Federal Reserve Bank of New York, 2014)
We provide a novel methodology for estimating time-varying weights in linear prediction pools, which we call dynamic pools, and use it to investigate the relative forecasting performance of dynamic stochastic general equilibrium (DSGE) models, with and without financial frictions, for output growth and inflation in the period 1992 to 2011. We find strong evidence of time variation in the pool's weights, reflecting the fact that the DSGE model with financial frictions produces superior forecasts in periods of financial distress but doesn't perform as well in tranquil periods. The dynamic pool's weights react in a timely fashion to changes in the environment, leading to real-time forecast improvements relative to other methods of density forecast combination, such as Bayesian model averaging, optimal (static) pools, and equal weights. We show how a policymaker dealing with model uncertainty could have used a dynamic pool to perform a counterfactual exercise (responding to the gap in labor market conditions) in the immediate aftermath of the Lehman crisis.
Keywords: C53; E31; E32; E37; 330; Bayesian estimation; DSGE models; financial frictions; forecasting; Great Recession; linear prediction pools; Wirtschaftsprognose; Prognoseverfahren; DSGE-Modell; Finanzkrise; Weltwirtschaftskrise; Theorie; Prognose; Welt